Determining Laying Hens Production Performance Using Analytical Hierarchy Process and Simple Additive Weighting Methods - Pradana, Andaka Dadi; Dewi, Findra Kartika Sari; Santoso, Albertus Joko (Universitas Atma Jaya Yogyakarta, 2020)
Abstract. The high consumption of chicken eggs in Indonesia must be balanced with the productivity level of laying hens to avoid scarcity resulting in an increasing price of chicken eggs. The maximum egg production can be possibly achieved by implementing a system of grouping chickens into good quality and poor performance different groups. This grouping can be made with a decision support system using the Analytical Hierarchy Process and Simple Additive Weighting methods. The criteria used in this test are eggs total, total of hens per coop, age, and hens’ death per coop. Alternatives used are coop 1, 2, 3, and 4. The coops were chosen as the alternative for the breeders compared the laying hens’ production performance based on the production per coop. The testing results, with the same input, show the same ranking order for both methods. The ranking order respectively the best to the worst is coop 1, coop 3, coop 2 and coop 4.Keywords: Laying hens, production performance, decision support system, Analytical Hierarchy Process, Simple Additive Weigthing.Abstrak. Banyaknya konsumsi telur ayam di Indonesia, harus diimbangi dengan tingkat produktivitas ayam petelur agar tidak terjadi kelangkaan yang mengakibatkan kenaikan harga telur ayam. Produksi telur yang maksimal bisa dicapai dengan menerapkan sistem pengelompokan ayam-ayam dengan kualitas performa yang baik dan yang kurang baik. Pengelompokan ini bisa dibuat dengan sistem pendukung keputusan menggunakan metode Analytical Hierarchy Process dan Simple Additive Weighting. Kriteria yang digunakan dalam pengujian ini adalah Total telur, Total ayam per kandang, umur ayam dan kematian ayam per kandang. Alternative yang digunakan adalah kandang 1, 2, 3, and 4. Kandang dipilih sebagai alternative karena peternak membandingkan performa produksi ayam petelur berdasarkan produksi per kandangnya. Hasil pengujian, dengan masukan yang sama, menunjukkan hasil perangkingan dengan urutan yang sama untuk kedua metode. Rangking terbaik sampai dengan terburuk, secara berturut-turut: kandang 1, kandang 3, kandang 2 dan kandang 4.Kata Kunci: Ayam Petelur, Performa Produksi, Sistem Pendukung Keputusan, Analytical Hierarchy Process, Simple Additive Weigthing.